The Influence Of Organisational Culture And Work Environment On Employee Performance Of The Housing, Settlement And Transportation Office In Seluma Regency - Puspita, Rola; Susanti, Neri; Nasution, Suswati (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2025)
The aim of this research is to determine the influence of organizational culture and work environment on the performance of employees of the Housing, Settlement and Transportation Department in Seluma Regency. This type of research is a type of quantitative descriptive research. The data collection method in this research uses a questionnaire technique, with a sample of 62 respondents. The research results show that multiple linear regression Y = 22,385 + 0.134 X1 + 0.444 X2 + 3,290. Where the coefficient is positive, meaning that there is a positive or unidirectional relationship between the organizational culture variable (X1) and the work environment, on employee performance at the Housing, Settlement and Transportation Service Office in Seluma Regency. The results show that the organizational culture test (XI) shows tcount 3.035 > ttable 1.669 and significance 0.004 < 0.05, then the results of the Ha hypothesis are accepted and Ho is rejected, meaning that organizational culture has a positive and significant effect on employee performance (Y) at the Housing, Settlement and Transportation Service Office in Seluma Regency. This means the hypothesis is accepted. The results of the work environment test (X2) show tcount 7.123 > ttable 1.669 and significance 0.000 < 0.05, so the results of the hypothesis Ha are accepted and Ho is rejected, meaning the work environment (X2) has a positive and significant effect on employee performance (Y) in the Service Office Housing, Settlement Areas and Transportation in Seluma Regency. The result of the Fcount value with Ftable is that the Fcount value is greater than the Ftable value, namely 29,056 > 2.75, so it can be concluded that Accepting the Hypothesis, meaning that there is a simultaneous influence between organizational culture (XI) and the work environment (X2) on employee performance (Y) in the Office Department of Housing, Settlement Areas and Transportation in Seluma Regency.